A COMPLETE EVALUATION OF MANVENDRA NATH RAI POLITICAL THOUGHT IN THE PRESENT CONTEXT (International Journal of Food and Nutritional Sciences, 2022)
Manabendra Nath Roy (M.N. Roy), a firebrand revolutionary who later became aphilosopher, left an indelible mark on Indian political thought. His journey, fromadvocating communist revolution to championing "Radical Humanism," compels us toconsider his ideas in the context of contemporary challenges.From Marxism to Radical Humanism: A Shift in FocusRoy's early years were steeped in revolutionary fervor. He saw Marxism as the answer toIndia's colonial subjugation. However, disillusioned by the Soviet model's rigidity, hedeveloped Radical Humanism. This philosophy emphasized reason, individual freedom,and a scientific outlook over dogma. Roy believed these were crucial for India's socialand economic progress.Relevance in the 21st CenturySeveral aspects of Roy's thought resonate in the present: